Subclavian artery cannulation provides superior outcomes in patients with acute type-A dissection: long-term results of 290 consecutive patients (Swiss Medical Weekly, 2013)
OBJECTIVES: The short-term results of subclavian artery cannulation (SC) for acute type-A dissection repair have been reported to be superior in regard to mortality and neurological outcomes when compared to femoral cannulation (FC). This study evaluates the long-term results of subclavian artery cannulation versus femoral cannulation for repair of acute type-A dissection with particular regard to neurological deficits, mortality and the need for re-operations. METHODS: From 1992–2005, 346 patients underwent surgical repair of acute type-A dissection of which 290 patients survived the operation. SC was performed in 114 patients and FC in 176 patients. Follow-up (FU) was completed in 89.5% (n = 259) and the medium FU-period was 42 months (SC) and 69 months (FC). Endpoints were persistence of neurological-deficits, mortality, major complications and necessity for re-operations. RESULTS: Overall survival and disease-free survival at 5 years were significantly higher in the SC group (83% vs. 71%; p = 0.022 and 74% vs. 61%; p = 0.044). Freedom of re-operation also appeared to be higher in the SC group (89% vs. 79%; p = 0.125). During the follow-up period, 28 patients (11/114 vs. 17/176; p = 0.58) suffered from neurological deficits of which 16 patients had permanent neurological-deficits at the 5 year follow-up. Of these patients, significantly more belonged to the FC group indicating an improved neurological-outcome for the SC group (3/11 vs. 13/17; p = 0.019). CONCLUSIONS: This study demonstrates excellent long-term outcomes after emergency surgery for acute type-A dissection. Subclavian artery perfusion represents an excellent approach to repair acute type-A dissection. Beside a significantly reduced long-term mortality, this technique provides an improved neurological outcome and a higher disease-free survival-rate.